Dietary Supplementation With Creatine Pyruvate Alters Rumen Microbiota Protein Function in Heat-Stressed Beef Cattle - Li, Yanjiao; Zang, Yitian; Zhao, Xianghui; Liu, Lin; Qiu, Qinghua; Ouyang, Kehui; Qu, Mingren (Frontiers in Microbiology, 2021)
Creatine pyruvate (CrPyr) is a new multifunctional nutrient that can provide both pyruvate and creatine. It has been shown to relieve the heat stress of beef cattle by improving antioxidant activity and rumen microbial protein synthesis, but the mechanism of CrPyr influencing rumen fermentation remains unclear. This study aimed to combine 16S rDNA sequencing and metaproteomics technologies to investigate the microbial composition and function in rumen fluid samples taken from heat-stressed beef cattle treated with or without 60 g/d CrPyr. 16S rDNA sequencing revealed that there was no significant differences in the α-diversity indices between the two groups. By analyzing the level profiles of 700 distinct proteins, we found that the CrPyr administration increased the expression of enzymes involved in specific metabolic pathways including: (i) fatty acid β-oxidation; (ii) interconversion from pyruvate to phosphoenolpyruvate, oxaloacetate, acetyl-CoA and malate; (iii) glycolysis/gluconeogenesis and citrate cycle metabolism; and (iv) biosynthesis of amino acids. These results indicated that the increased generation of ATP during fatty acid β-oxidation or citrate cycle and the up-regulation synthesis of microbial protein in rumen of beef cattle treated with CrPyr, may help decreased oxidative stress, regulate energy metabolism, and further improve the rumen fermentation characteristic under heat stress.